What Linked Data Can Tell Us About the Increasing Numbers of Children Entering Public Care. - Warner, Nell; Forrester, Donald; Scourfield, Jonathan; Cannings‐John, Rebecca; John, Ann (Child & Family Social Work, 2026)
The number of children in public care in Wales, UK, rose from the mid‐1990s to 2021. It is unclear if this change was related to increases in risk factors in parents, changes in the impact of risk factors, or changing policies and practices. Administrative data from children's social care were linked to administrative health care data to create three cohorts of households with children, covering 4‐year periods between 2008 and 2020. Households that had at least one child aged 3–17 enter care in each cohort were identified, as were health‐related risk factors in adults in households: mental health, substance misuse and neurodivergence. Across each of the cohorts, the prevalence, attributable fractions and excess cases were calculated for each health‐related risk factor. Logistic regression models explored the impact of health‐related risk factors on the likelihood of care. Depression and anxiety showed the greatest increase in prevalence, and these account for some of the increase in later cohorts. The impact of depression on the odds of care also increased. For several other health‐related risk factors, for example, parental drug use and severe mental health issues, there was no increase over time in either prevalence or impact on care entry.